Graphene: Synthetic Multifunctional Graphene Composites with Reshaping and Self‐Healing Features via a Facile Biomineralization‐Inspired Process (Adv. Mater. 34/2018). Issue 34 (20th August 2018) - Lin, Shuyuan; Zhong, Yujia; Zhao, Xuanliang; Sawada, Toshiki; Li, Xinming; Lei, Wenhai; Wang, Moran; Serizawa, Takeshi; Zhu, Hongwei
Abstract : Inspired by the biomineralization process, a shapeable, multi‐manipulatable, and recyclable gel‐like graphene oxide macroscopic assembly is prepared by Takeshi Serizawa, Hongwei Zhu, and co‐workers in article number1803004 . This assembly is stretchable, malleable, self‐healable, and easy to process in the wet state, but tough and rigid in the dried state. These two states can be readily switched by adjusting the water content, which shows the advantage of recyclability and it can be used for 3D printing to form varied architectures.